Functional fitness and cognitive performance in independent older adults – Fallers and Non-Fallers: An exploratory study - Bravo, Jorge (2018)
Background Actual research reinforces the importance of multimodal exercise pro- grams for fall prevention; however remains unclear which components should be included in exercise programs, considering physical and cog- nitive components. Objectives This exploratory study aims to identify the associations between functional fitness (FF) and cognitive performance (CP) in independ- ent older adults, regarding fallers and non-fallers. Methods 63 males and 124 females (65-96 years) were selected based on the cri- teria of moderate or high functional independency (≥18 points) deter- mined by responses to the 12-item of Composite Physical Functioning Scale [1]. FF was assessed by the Senior Fitness Test Battery [2]. A com- posite Z-score was created based on the individual scores for each fit- ness item. CP was assessed by the Mini-mental State Examination adapted for the Portuguese population [3]. Descriptive statistics were calculated for all outcome measurements and comparisons were per- formed using independent sample t-Tests. Multiple regression analyses were performed to test associations between FF and CP. Results T-test comparisons showed that females were more flexible than males (p < 0.05). Males were taller and heavier than females (p < 0.05). No dif- ferences were observed between these independent fallers and non- fallers sample. Multiple regression analyses were performed to under- stand the association of FF with CP in fallers and non-fallers. Agility was negatively associated with the MMSE score in fallers and non-fallers; however, after adjusting for gender, age and education, this association was not significant for non-fallers (p < 0.05). Lower body strength showed positive associations (p < 0.05) with the MMSE score exclu- sively in non-fallers, regardless the adjustments. Likewise, the upper body strength was positively associated with the MMSE score (p < 0.05) in non-fallers after adjusting for age, gender and education (p < 0.05). On the other hand, the upper body flexibility showed negative associa- tions with the MMSE score (p < 0.05) however this association did not remain significant after adjusting for gender, age and education. Conclusions Independent older adults with higher agility scores were more likely to have an improved CP, whether they are fallers or non-fallers. Body strength, particularly improved lower body strength, is associated with higher CP in non-faller older adults, independently of age, gen- der and education. This exploratory study increases the spectrum of research in multimodal programs by suggesting that agility and strength training should be included in exercise prescription for fall prevention, in order to foment CP.